Persistência de lactação e composição do leite de cabras Saanen alimentadas com rações formuladas por diferentes comitês - Marcus Vinicius da Fonseca (2014)
The experiment was conducted to evaluate and compare the composition and production of Saanen goats milk fed diet formulated using the values tabulated by three different committees of nutritional requirements, also comparing the persistence of lactation goats. Thesystems used to generate values were nutritional requirements (NRC, 2006); AFRC (1993) and INRA (1988). The experimental period was 180 days, between 72 days up to 252 days of lactation. 30 animals were used in a randomized block design. The power control was performed daily, with samples analyzed for the levels of dry matter, ash, crude protein, ether extract, neutral detergent fiber, acid detergent fiber, cellulose, hemicelluloses. During the lactation period was controlled every 15 days, milk production and samples were collected for analysis of total solids, protein, fat and lactose and somatic cells. The consumption values ofpredicted dry matter in feeding systems were compared to those obtained under experimental conditions. Resulting in differences in consumption observed values in relation to predicted on all systems. The average milk yield observed for each treatment (NRC, AFRC, INRA)were, respectively, 2.59, 2.46, 2.52 kg / day. When it treatment of economic cost between AFRC diets showed better average rate of return, net present value and benefit cost, then the treatment NRC and finally the INRA treatment.